Security Mindset Fundamentals and Second Language Learning (Journal of The Colloquium for Information Systems Security Education, 2023)
Security mindsets can be said to engage elements of situational awareness and analytical, creative, and practical elements of adversarial thinking. Scholars have debated whether this is taught or fostered, but they have acknowledged that security mindsets are critical. Here, the argument is made that implicit features of language itself can be drawn on in everyday K12+ second language (L2) learning settings to introduce members of the general populace and, among them, potential future members of the cybersecurity workforce, to security thinking. Beyond the features of language itself, L2 lessons can also be adapted to familiarize students with explicit security-related topics and scenarios. By exploiting these novel connections between language learning and security thinking, L2 learning contexts can become a security mindset training ground for millions of U.S. students.
Keywords: security mindset; adversarial thinking; situational awareness; second language learning; K12+; cybersecurity for non-cyber students; inclusion and diversity